4 Extracellular volume in the infarct zone is associated with clinical and mri measures of infarct severity in survivors of acute stemi. (26th April 2015) - Carberry, J; Carrick, D; Haig, C; Rauhalammi, SM; Ahmed, N; Mordi, I; McEntegart, M; Petrie, M; Eteiba, H; Hood, S; Watkins, S; Lindsay, M; et al.
Abstract : Background: The clinical significance of extracellular volume (ECV) expansion in infarcted myocardium post-STEMI is unknown. Myocardial ECV can be estimated by cardiac magnetic resonance imaging (CMR) using T1 MOLLI maps before and after contrast. We repeatedly measured infarct ECV in STEMI survivors, and assessed the relationships between ECV, peak troponin T and baseline infarct size. Methods: Acute STEMI survivors were enrolled in a single-centre cohort study (BHF MR-MI study – NCT02072850 ). Contrast-enhanced CMR was performed at 1.5 Tesla (Siemens MAGNETOM Avanto) 2 days and 6 months post-MI. T1 mapping with MOLLI was performed before and 15 min after contrast (0.15 mmol/kg gadoterate meglumine). ECV analysis was performed by outlining regions of interest (ROIs) in infarcted myocardium and left ventricular (LV) blood pool. ROIs were representative of the infarct including microvascular obstruction. ECV was calculated as the relaxation rate (R1=1/T1) for myocardium and LV blood pool before vs. after contrast, corrected for haematocrit. Infarct size was measured using late gadolinium images and expressed as a percentage of LV mass. Infarct ECV at baseline and follow up was compared with peak troponin T measured at presentation and infarct size at baseline. Peak troponin T was log-transformed to improve normality and linearity. Results: 201 STEMI patients (mean age 58 ± 11 years; 156 (77%) male) were enrolled. Infarct ECV was similar at baseline and follow-up (51.3 ± 9.5% vs. 50.3 ± 12.0%, p = 0.097). Peak troponin T was widely variable (4256.7 ug/L ± 4020.8 ug/L). Peak troponin T was positively associated with infarct ECV at baseline (p < 0.001) and follow-up (p < 0.001). Infarct size at baseline was 18 ± 13% of LV mass and was positively associated with infarct ECV at baseline (p < 0.001) and follow-up (p < 0.001) (Table 1 ). Conclusion: High peak troponin T and a large infarct size are predictors of higher infarct ECV at baseline and follow-up. Infarct ECV is associated with clinical and MRI measures of MI severity in survivors of STEMI.